Fighting cervical cancer through awareness communication plan for cervical cancer awareness among senior high school female students in Luzon, Governor Generoso, Davao Oriental - Taypin, Lornille Faith A.; Comidoy, Merle Dawn S. (2019)
Cervical cancer is the second leading cancer site among women in the Philippine according to the Department of Health (2018). However, lack of awareness of this deadly disease has been a continuing problem in Luzon, Governor Generoso, Davao Oriental, including Luzon National High School senior high school female students. Baseline data from the Luzon Health Center showed that these senior high school female students only exposure to cervical cancer awareness, prevention, and the detection was from a small talk delivered by the nurse or midwife but these students barely attended the talk. Hence, the study aimed to produce a communication plan to help improve the Luzon Health Center school-based campaigns in raising awareness on cervical cancer among senior high school female students in Luzon, Governor Generoso, Davao oriental. The study used mixed method - a survey of 103 LNHS senior high school female students for the quantitative and a focus group discussion with the midwife and Barangay Health Workers (BHWs) for the qualitative method. Formative research showed that SHS female students have low awareness level and health beliefs on cervical cancer and BHWs stressed that although they have been conducting services against cervical cancer, they haven't conducted awareness programs for students. With these, the researcher created a communication plan- a one year awareness program by the Luzon Health Center in collaboration with Luzon National High School that was suggested to be implemented from August to May, with interventions such as forums, poster distribution, film/documentary viewing, short video production and other fun-filled yet productive and enriching activities. Ways to evaluate the interventions were also provided
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019